PENGARUH DISIPLIN DAN KOMPETENSI TERHADAP KINERJA BENDAHARA SKPD DI KABUPATEN MERANGIN - Siti Aminah; Eko Suprapto (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This study aims to identify and analyze the performance Bendahara SKPD Kapupaten Merangin. Relative to the employee how to work with the Bendahara SKPD as possible and have the discipline and high competence in completing the work at the time of making the annual financial statements will be submitted to the BPKD. So on this, the study aims to demonstrate the significance of the influence of Discipline and Competence of the Bendahara SKPD's performance . In analyzing the data used descriptive analysis of the distribution that contains the items of each variable, then simple linear regression analysis and hypothesis testing. From the test results with a simple linear regression and partial regression analysis showed that the simultaneous discipline variable (X1) effect on the performance of 6533 (Y) and significant treasurer of 0.000. This shows that t = 6533> table = 1,671 or 0,000 significant <0.05, according to the first hypothesis, the results show that H0 is rejected and H1 is accepted, ie Discipline (X1) have a significant effect on performance (Y) Bendahara SKPD Kabupaten Merangin. Competence variable (X2) effect of 2,101 on the performance (Y) and significant employees of 0.000. This shows that t = 2.101> table = 1,671 or 0,040 significant <0.05, according to the second hypothesis. The results showed that H0 is rejected and H1 is accepted, namely competence (X2) have a significant effect on performance (Y) Bendahara SKPD Kabupaten Merangin. R-value test results of .735 and .540 R Square valuable. This shows that the multiple correlation (Discipline X1 and X2 competence) on employee performance. R2 value 0.540 indicates the role or contribution of Discipline and competence variables were able to explain the variable performance of 54%. While the rest of 46% is influenced by other variables not included in this study.Keyword: Discipline, Competence, performance